LIVING THE NEW MEANING OF THE MENTAL SICK PERSON CONCEPT THROUGH INTERPERSONAL THERAPEUTIC RELATIONSHIP: A REPORT OF EXPERIENCE - Daniele Akemi Arita; Ana Lúcia Fonseca; Maria Neiva Ribeiro Barbosa Faleiros (Universidade Federal do Paraná, 2002)
This concerns about a report of experiences lived during nursing theoretical- practical classes in Mental Health of Federal University of Paraná, at a psychiatric hospital in Curitiba with a female patient chosen randomly. It was given emphasis to the therapeutic student-patient relationship with the objective of reduce the initial felling of fear and demystify the pre-concepts that the society externalizes about the lived reality of the mental sick person. During the therapeutic interaction, I could observe and live all the fear and insecurity that, not only me as a student, but also the patient showed during the firsts days of our relationship. It was possible, at the end of the developed therapeutic student-patient relationship, that is the nursing care base, to establish a link through mutual trust and, consequently, to overcome the fear of taking care of a psychiatric patient.